Functional Complete Revascularization as Determined by an Optimized Scoring System After Revascularization: A Post Hoc Analysis from Multi‐Center PANDA III Trial - Rui Zhang; Shaoyu Wu; Qianqian Liu; Changdong Guan; Hao‐Yu Wang; Sheng Yuan; Lihua Xie; Yunfei Huang; Zheng Qiao; Weida Liu; Rui Fu; Lei Feng; et al. (Advanced Science)
Abstract Functional complete revascularization (CR) after percutaneous coronary intervention (PCI) as determined by classic residual functional SYNTAX score (c‐rFSS) has been associated with improved prognosis. In this study, the c‐rFSS algorithm is optimized for a novel modified rFSS (m‐rFSS) and prognostic implications of this novel scoring is determined. The m‐rFSS algorithm is updated for 2 clinical scenarios, i.e., 1) lesions with suboptimal functional results, and 2) angiographic diameter stenosis <50% but functionally significant stenoses, which are not scored by c‐rFSS. The major outcome is a 2‐year major adverse cardiac event (MACE). A total of 1,555 patients analyzable for both c‐rFSS and m‐rFSS are included. After calculating m‐rFSS, 12.0% (187/1,555) of patients with c‐rFSS‐based functional CR (c‐rFSS = 0) are reclassified as having m‐rFSS‐based incomplete revascularization (IR, m‐rFSS>0); thus, 377 (21.7%) patients have c‐rFSS‐based functional IR whereas 524 (33.7%) has m‐rFSS‐based IR. Patients with m‐rFSS‐based functional IR (m‐rFSS>0) show a significantly higher risk for major MACE outcome (20.8% vs 5.9%; adjusted hazard ratio 3.32, 95% confidence interval: 2.34–4.71) than patients with functional CR (m‐rFSS = 0). The m‐rFSS is more predictive of 2‐year MACE than c‐rFSS (difference in C‐index 0.07, p < 0.001). In this study, we optimized the classic scoring algorithm to develop a novel scoring system (m‐rFSS), and revascularization completeness determined by m‐rFSS is markedly associated with a 2‐year prognosis.